HUBUNGAN FAKTOR PERILAKU DENGAN KEJADIAN KARIES GIGI ANAK USIA 12 TAHUN DI SMP TRI BHAKTI PEKANBARU TAHUN 2018 - Muhti Wibowo, Alhidayati, Syukaisih (Menara Ilmu, 2019)
Dental caries is dental system disease that marked by system damaged, starting from thetooth surface (niche, fissure, and interproximal area) extending towards the pulp (Brauer).Based on data from WHO in 2016, children aged 12 yearsold 76,97% experience dentalcaries cases. Data from Basic Health Research in 2015, amount of caries is 72,1%. Datafrom Health Officer Pekanbaru City in 2017, amount of caries 2,78%, while data fromPayung Sekaki Public Health Center, caries owned by students Tri Bhakti Junior HighSchool Pekanbaru with amounted 52 students in 2017. This research which is used is analyticquantitative with cross sectional design, and sample which is researched amounted 88 prsonswith measurement equipment is questionnaire, analysis which is used is univariat andbivariat. Result of statistic test using Chi Square test obtained, knowledgeP value = 0,003 (Pvalue≤ α0,05), Attitude P value = 0,000 (P-value ≤ α0,05), Sweet food behavior P value =0,001 (P-value ≤ α0,05), Frequency of brushing teeth P value = 0,001 (P-value ≤ α0,05),Selection of toothbrush P value = 0,000 (P-value ≤ α0,05), Parents role P value = 0,001 (Pvalue≤ α0,05).It can be concluded, there are meaningful correlations among knowledge,attitude, sweet food behavior, frequency of brushing teeth, selection of toothbrush, parentssrole, with incidence of dental caries on children aged 12 years old in Tri Bhakti Junior HighSchool Pekanbaru in 2018, also students are suggested to always maintain dental hygiene toavoid dental caries / cavities.Keywords : Dental Caries, Caries Data, Students of Tri Bhakti Junior High School